Co-Crystal Screening of Diclofenac - John Desper; Christer B. Aakeröy; Angela B. Grommet (MDPI AG, 2011)
In the pharmaceutical industry, co-crystals are becoming increasingly valuable as crystalline solids that can offer altered/improved physical properties of an active pharmaceutical ingredient (API) without changing its chemical identity or biological activity. In order to identify new solid forms of diclofenac-an analgesic with extremely poor aqueous solubility for which few co-crystal structures have been determined-a range of pyrazoles, pyridines, and pyrimidines were screened for co-crystal formation using solvent assisted grinding and infrared spectroscopy with an overall success rate of 50%. The crystal structures of three new diclofenac co-crystals are reported herein: (diclofenac)∙(2-aminopyrimidine), (diclofenac)∙(2-amino-4,6-dimethylpyrimidine), and (diclofenac)∙(2-amino-4-chloro-6-methylpyrimidine).